Dyslipidaemia in Schizophrenia - Hasan, Syeda Marufa; Sultana, Nasima; Awual, SM Abdul; Ferdous, Shamim Are; Amiruzzaman, Molla (Anwer Khan Modern Medical College Journal, 2021)
Background: Lipid neurochemistry is an important focus in schizophrenia research. Disorder of fatty acid metabolism within the brain tissue play an important role in the pathophysiology of schizophrenia. Material & Methods: To evaluate the association of dyslipidaemia with Schizophrenia and compare the serum lipid profile with healthy individuals, a cross sectional analytical study was conducted between July 2011 and June 2012 in the Department of Biochemistry, Dhaka Medical College, following approval of a protocol. As per criteria, total 100 cases were included in this study and divided into two groups: Group-I (Diagnosed cases of schizophrenia) and Group-II (Healthy individuals). Written informed consent was taken from all cases. Serum lipid profile (Total Cholesterol, Triglycerides, HDL and LDL) was estimated from both groups by enzymatic determination. Result: Fasting serum triglyceride (p<0.03), HDL cholesterol (p<0.001) and LDL cholesterol (p<0.001) between the groups are significantly related. In group-I mean serum HDL cholesterol is reduced, but LDL cholesterol and Triglyceride were elevated in comparison with group-II. No significant relationship was observed in fasting serum total cholesterol in between groups (p>0.05). Result indicates strong association between schizophrenia and dyslipidaemia. That association would increase the risk of developing coronary heart disease in those patients with schizophrenia compared with healthy individual. AKMMC J 2022; 13(1) : 8-13